Genome-Wide Characterization and Comprehensive Analysis of NAC Transcription Factor Family in Nelumbo nucifera - Song, Heyun; Liu, Yanling; Dong, Gangqiang; Zhang, Minghua; Wang, Yuxin; Xin, Jia; Su, Yanyan; Sun, Heng; Yang, Mei (Frontiers in Genetics, 2022)
NAC (NAM, ATAF, and CUC) is a ubiquitously expressed plant-specific transcription factor (TF) family which is involved in the regulation of various biological processes. However, a systematic characterization of NAC gene family is yet to be reported in lotus. Here, 82 NnNAC genes which included five predicted membrane-bound NAC proteins were identified in the lotus genome. Phylogenetic analysis revealed seven-subfamily clusters (I-VII) of NnNAC proteins, with homologous gene pairs displaying similar conserved motifs and gene structure characteristics. Transactivation assay of NnNAC proteins revealed an extensive transcriptional activation capacity which is mediated by the highly divergent C-terminal activation domain (AD). Expression analysis of NnNAC genes in lotus tissues showed high transcript levels in root, stamen, petal and seed coat. In addition, 30 and 29 differentially expressed NnNAC candidate genes putatively involved in lotus seed development and response to complete submergence stress, respectively, were identified. Overall, our study provides potentially useful candidate gene resources for future molecular breeding of lotus varieties with novel agronomic traits.